PERSEPSI GURU MENGENAI PELAKSANAAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) BERKARAKTER DI SMA PGRI 2 PADANG TAHUN 2012/2013 - Yuliadi, Afri; Ansofino, M.Si, Dr.; Areva, S.Pd, Desi (Pendidikan Ekonomi, 2014)
ABSTRACT In the application of the Education Unit Level Curriculum (EULC) that occur in the field of perception irregularities in the implementation of the educational unit level curriculum EULC character and obstacles faced by teachers in preparation for the EULC unit level curriculum character education and the efforts made to overcome these obstacles This research was conducted in SMA PGRI 2 Padang . This research is a descriptive study , population and sample in this study were all high school teachers PGRI 2 Padang as many as 37 teachers . The type of data retrieved form the primary data and skuder . Techniques of data collection by using questionnaires , interviews , documentation . To measure teacher perception variables to curriculum Tertiary education unit used scale measuring tool liqueur . The data analysis technique used is the descriptive statistical analysis techniques .The results showed that the overall perception of teachers regarding curriculum EULC either . It can be seen on the basic concept of EULC based on knowledge with an average of 88.29 % and 72.16 % based on attitude , scope of EULC based on knowledge with an average of 91.44 % and 81.35 % based on the attitude , the learning process is based on knowledge with an average 89.9 % and 74.73 % based on attitude , EULC based knowledge assessment system with an average of 90.54 % and 60.54 % based on attitudes , knowledge barriers to the implementation of EULC based on average 89.19 % and 75.5 % based on attitude , as for the suggestion that the writer can convey is hendakmya Teacher to prepare and learn first all of the EULC. To the principal as a leader in the school should have to fully support the implementation of EULC in order to run smoothly and to the school to be able to create and add a quality school facilities and infrastructure to support the implementation of the EULC.